2019
DOI: 10.7717/peerj.7384
|View full text |Cite
|
Sign up to set email alerts
|

Integrating phylogeographic and ecological niche approaches to delimitating cryptic lineages in the blue–green damselfish (Chromis viridis)

Abstract: Species delimitation is challenging in sibling species/cryptic lineages because of the absence of clear diagnostic traits. However, integration of different approaches such as phylogeography and ecological niche comparison offers one potential approach to tease apart recently diverged lineages. In this study, we estimate the ecological niche divergence among lineages in Chromis viridis in a broad-scale phylogeographic framework to test whether the combination of these two approaches can effectively distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…S1). This finding is congruent with the results of connectivity studies targeting damselfishes between the SCS and Kuroshio regions which showed low and non-significant genetic structure among the Xisha (Paracel) Islands, Dongsha, and Taiwan (Liu et al, 2011(Liu et al, , 2014(Liu et al, , 2019. Failure to reject panmixia is generally common in marine species (Waples, 1998;Kinlan & Gaines, 2003), has been found consistently in the Indo-Pacific (Keyse et al, 2014;Crandall et al, 2019a), and is traditionally interpreted as evidence for relatively high levels of gene flow due to larval dispersal.…”
Section: Discussionsupporting
confidence: 84%
“…S1). This finding is congruent with the results of connectivity studies targeting damselfishes between the SCS and Kuroshio regions which showed low and non-significant genetic structure among the Xisha (Paracel) Islands, Dongsha, and Taiwan (Liu et al, 2011(Liu et al, , 2014(Liu et al, , 2019. Failure to reject panmixia is generally common in marine species (Waples, 1998;Kinlan & Gaines, 2003), has been found consistently in the Indo-Pacific (Keyse et al, 2014;Crandall et al, 2019a), and is traditionally interpreted as evidence for relatively high levels of gene flow due to larval dispersal.…”
Section: Discussionsupporting
confidence: 84%
“…Chromis xanthochira XIII dorsal spines; similar to C. weberi (Moyer and Ida, 1976;Randall et al, 1981Randall et al, , 1997Myers, 1999) and C. xanthura (Moyer and Ida, 1976) S3) discovered genetically distinct populations in the Indian and Pacific basins (their ''Pattern 2''). Others have also found divergent lineages within C. atripectoralis and/or C. viridis (Hubert et al, 2012(Hubert et al, , 2017Messmer et al, 2012;Liu et al, 2019). The identity of the taxon identified as ''Chromis caerulea'' remains unclear.…”
Section: Chromis Xanthochiramentioning
confidence: 99%
“…The Kuroshio Current runs northwards to Japan from the bifurcation of the Northern Equatorial Current off the eastern coast of the Philippines [65] and may provide an avenue for migration, particularly from the core to the edge. Indeed, other damselfish show limited genetic differentiation between Japanese populations and those in the Coral Triangle [66]. However, the strong genetic differentiation seen between A. clarkii populations in Japan and the Philippines/Indonesia suggests these distinct genetic lineages may be maintained by local adaptation in addition to gene flow.…”
Section: (A) Life On the Edgementioning
confidence: 99%